Ginsenoside Rg1 Alleviates Podocyte Injury Induced by Hyperlipidemia via Targeting the mTOR/NF-κB/NLRP3 Axis. (9th October 2020) - Wang, Tao; Gao, Yanbin; Yue, Rongchuan; Wang, Xiaolei; Shi, Yimin; Xu, Jiayi; Wu, Bingjie; Li, Yimeng
Abstract : Background . Podocyte injury plays an important role in diabetic nephropathy (DN). The aim of this study was to determine the potential therapeutic effects of the ginsenoside Rg1 on hyperlipidemia-stressed podocytes and elucidate the underlying mechanisms. Methods . In vitro and in vivo models of DN were established as previously described, and the expression levels of relevant markers were analyzed by Western blotting, real-time Polymerase Chain Reaction (PCR), immunofluorescence, and immunohistochemistry. Results . Ginsenoside Rg1 alleviated pyroptosis in podocytes cultured under hyperlipidemic conditions, as well as in the renal tissues of diabetic rats, and downregulated the mammalian target of rapamycin (mTOR)/NF- κ B pathway. In addition, Rg1 also inhibited hyperlipidemia-induced NLRP3 inflammasome in the podocytes, which was abrogated by the mTOR activator L-leucine (LEU). The antipyroptotic effects of Rg1 manifested as improved renal function in the DN rats. Conclusion . Ginsenoside Rg1 protects podocytes from hyperlipidemia-induced damage by inhibiting pyroptosis through the mTOR/NF- κ B/NLRP3 axis, indicating a potential therapeutic function in DN.